Filling the gap: Long run Canadian wealth inequality in international context - James B. Davies; Livio Di Matteo (The University of Western Ontario, Department of Economics, 2018)
There is a gap in estimates of the personal distribution of wealth in Canada between 1902 and 1970. That gap is partly filled here, using estate multiplier estimates for 1946-1970 and survey results for 1970-2012. Estate multiplier estimates are adjusted for differential mortality, and the survey upper tails are adjusted in line with respected journalistic "rich lists". Top wealth shares decline from 1902 to 1970, similar to other advanced western countries. There is no trend since 1970, which contrasts with a rise in the United States. Reasons for this difference between Canada and the U.S. are considered.
Keywords: 330